Understanding ‘Children’s Construction of Biological Concepts’ and Its Educational Implications - MEHROTRA, ILA; BANIWAL, VIKAS (SCHOOL SCIENCE, 2006)
Young children possess knowledge about biological phenomenon. It enables them to make sense of what they observe about animals and plants.Motoyoshi (1979) reported that a five year old girl summarised her accumulated experiences with raising flowers by using the following analogy: “Flowers are like people. If flowers eat nothing (are not watered), they will fall down of hunger. If they eat too much (are watered too often), they will be taken ill. Motoyoshi (1979) has also reported an anecdotal example of causal attribution for an animal’s unusual physical reaction. He reported an example of five year old children in a day care centre. These children were taking care of a rabbit. When one day they observed an unusual excretion, they concluded that it might be suffering from diarrhoea, as a person might suffer from diarrhoea.